P52 How can we use liver ultrasound more efficiently with rising demands?. (20th September 2022) - McNeill, Lisa; Douglas, Aisling; Stenberg, Benjamin; McNeill, Michael; McPherson, Stuart
Abstract : Background: Given the large burden of undiagnosed liver disease in the community, there are calls to improve early detection to permit treatment and/or surveillance for complications. Ultrasound forms part of the work up for patients with suspected liver disease, but may not add much diagnostic value for some patients, such as those with fatty liver without advanced fibrosis/cirrhosis. With expansion of liver disease early detection programmes there is potential to overwhelm existing ultrasound services, reducing access to those with strong indications (e.g. HCC surveillance). The aim of this work was to review the indications for patients referred for outpatient liver ultrasound scans (USS) in our Trust to identify where the scans may not add significant additional diagnostic information, ultimately to create capacity for those with strong indications. Methods: All outpatient liver USS performed in October 2021 in our Trust were retrospectively reviewed looking at the indication and result. Scans were excluded if they were not targeted on the liver or were for abdominal pain or gallstones. Results: From a total of 1295 abdominal USS performed, 471 were liver targeted (314 [75%] secondary care [SC] and 157 primary care [PC]). Of the SC scans 138 (44%) were for HCC surveillance, 48 (15%) for investigation of suspected advanced fibrosis/cirrhosis, 34 (11%) for investigation of raised liver enzymes, 11 (4%) for suspected fatty liver and 83 (26%) other indications (e.g. HBV, HCV, PSC). Of the PC scans, 73 were to investigate raised liver enzymes (38 [52%] hepatitic, 31 cholestatic, 3 mixed, 1 isolated raised bilirubin), 34 were suspected fatty liver, 18 were for suspected advanced fibrosis/cirrhosis and 32 were for other indications. Of the 34 PC scans carried out for primarily for suspected fatty liver, 27 had a FIB-4 calculated and 23 (85%) had a FIB-4 <1.45. Of these, 22 had fatty liver confirmed on USS and 1 was normal. There were no other significant findings on any of these scans. Additionally, of the 38 patients with hepatitic blood tests, 20 patients had fatty liver on USS and only 4 had FIB-4 score >1.45. Conclusions: A significant number of USS from primary care were for patients with suspected fatty liver with low FIB-4 and ultrasound yielded no additional findings in these patients. To help create capacity in ultrasound we plan to modify our regional guidance to advise against routine ultrasound for patients with suspected fatty liver with low FIB-4 and no additional symptoms.